2005
DOI: 10.1002/j.0022-0337.2005.69.4.tb03932.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Residency Directors’ Knowledge and Attitudes About Pediatric Oral Health Education for Residents

Abstract: The Surgeon General's report on oral health called for improved education about oral health, a renewed understanding of relationships between oral and overall health, and an interdisciplinary approach to oral health involving primary care providers. This study examined the following: 1) family medicine residency directors' knowledge of preventive dental care, 2) status of an oral heath curriculum in family medicine residencies, and 3) the likelihood of initiating an oral health curriculum. We conducted a fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…The results showed that less than 30% of the program directors felt comfortable with the application of fluoride varnish. The program directors felt this way because of the lack of knowledge on children’s oral health and it was concluded that 95% of family medicine program directors believed oral healthcare knowledge should be a component in the residency training ( 30 ).…”
Section: Background and Rationalementioning
confidence: 99%
“…The results showed that less than 30% of the program directors felt comfortable with the application of fluoride varnish. The program directors felt this way because of the lack of knowledge on children’s oral health and it was concluded that 95% of family medicine program directors believed oral healthcare knowledge should be a component in the residency training ( 30 ).…”
Section: Background and Rationalementioning
confidence: 99%
“…Nevertheless, few studies 11 , 12 examined a physician's role in identifying, discussing, or preventing oral disease and only focused on children. With the aim of assessing oral health knowledge and orientations of physicians in training, we surveyed internal medicine trainees about their general knowledge, attitudes, and behaviors/practices about periodontal health and disease.…”
mentioning
confidence: 99%
“…Optimum timing of the first dental check-up, for example, can be communicated to parents during well-child visits, which are mandatory for all preschool children after birth. It has been reported that physicians and nurses have the opportunity to provide oral care for preschool children seven times more frequently than dentists, especially those at high-risk for ECC as a result of well-child visits [22]. Interaction between members of the medical and dental communities is consequently crucial to help refer preschool children at high risk for ECC, especially those who do not have a dental home but have an established medical one [23,24].…”
Section: Discussionmentioning
confidence: 99%